Overview of ISO 14001 certification in the northern region of Brazil (Research, Society and Development, 2020)
This research aimed to present an overview of the ISO 14001 certification in the Northern region of Brazil, in order to systematize existing data and provide organized information on the subject. The secondary data used are the national base of the Brazilian conformity assessment system managed by INMETRO. The results showed that the North region, in general, presented a low interest for ISO 14001 certification when compared to the other Brazilian regions. Among the northern states, Amazonas had the highest number of certificates. In 2017, Brazil registered 2.128 certifications, of which only 5% were in the North region. It was also verified that the transformation industries constitute a significant portion of the total percentage of certified companies, totaling 73%. It was also observed a gradual decrease in the number of certifications from 2015, mainly explained by the update of the base NBR in that year, and as well as result of the context of economic crisis faced by the country.